2003
DOI: 10.1097/00005537-200302000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steel Scalpel, Ultrasonic Scalpel, CO2 Laser, and Monopolar and Bipolar Electrosurgery on Wound Healing in Guinea Pig Oral Mucosa

Abstract: Use of the ultrasonic scalpel produced faster re-epithelialization and greater tensile strength than laser or electrosurgical instruments, with results comparable to those seen with the steel scalpel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
1
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(165 citation statements)
references
References 68 publications
6
139
1
9
Order By: Relevance
“…En varios estudios, tanto en animales como en humanos, se comparan los efectos del bisturí convencional contra los del electrocauterio en diferentes tejidos, sin encontrar verdaderas diferencias ni clíni-cas ni estadísticas (11)(12)(13)(14)(15)(16). En el actual estudio se pudo determinar que aunque se presentaron en el 71,1% carbonización y coagulación en el tejido conectivo y un 77,8% de carbonización en el epitelio, solo se observa en el borde y se pueden ver todas las características necesarias como linfocitos, células plasmáticas, neutrófilos, para determinar la presencia de inflamación y entre otras características como espongiosis, balonización, atrofia etc, las cuales se presenten en el epitelio.…”
Section: Discussionunclassified
“…En varios estudios, tanto en animales como en humanos, se comparan los efectos del bisturí convencional contra los del electrocauterio en diferentes tejidos, sin encontrar verdaderas diferencias ni clíni-cas ni estadísticas (11)(12)(13)(14)(15)(16). En el actual estudio se pudo determinar que aunque se presentaron en el 71,1% carbonización y coagulación en el tejido conectivo y un 77,8% de carbonización en el epitelio, solo se observa en el borde y se pueden ver todas las características necesarias como linfocitos, células plasmáticas, neutrófilos, para determinar la presencia de inflamación y entre otras características como espongiosis, balonización, atrofia etc, las cuales se presenten en el epitelio.…”
Section: Discussionunclassified
“…Re-epithelisation grade was measured according to Sinha and Gallagher 2003 established criteria (Sinha and Gallagher 2003). Results were given in a semiquantitative manner with a score from 0 to 4.…”
Section: Histological Analysismentioning
confidence: 99%
“…At day 7 after wounding, in the rhEGF MS group re-epithelisation starts, partially covering the wound surface (according to Sinha et al 2003 criteria; 1.13 ± 0.35).…”
Section: Re-epithelisationmentioning
confidence: 99%
“…Few studies are reported in literature about the effect of thermal tissue injury in head and neck area, and the vast majority of them are based on animal or cadaveric models [11][12][13][14][15][16][17]; here, a laryngeal model, created using excised larynges, was developed to quantify the effect of thermal injury of different devices on laryngeal normal mucosa and to predict their effect on margins status and final histopathological report.…”
Section: Introductionmentioning
confidence: 99%